Resource allocation optimization algorithm based on double populations differential evolution in WSN - Xiaochen HAO; Liyuan WANG; Jinshuo LIU; Lixia XIE; Wenhuan ZHANG (Tongxin xuebao)
A resource allocation algorithm was proposed for improving the network performance through jointing channel allocation,power control and timeslot allocation in multi-radio multi-channel wireless sensor network.More specifically,the network was modeled as a multi-objective optimization problem where the energy efficient,resource allocation balanced,networks capacity maximized were considered under the link interference and link conflict constraints.Due to the problem was NP-Hardness,a simple centralized algorithm——differential evolution based on double populations was used to solve the constrained multi-objective optimization problem.The simulation results show that the proposed algorithm significantly improves the network capacity and energy efficiency and guarantees the resource allocation balancing while reducing link interference and avoiding link conflict.